Board diversity and firm value: A study on Malaysian listed firms in manufacturing and non-manufacturing sectors - Mohd Waliuddin, Mohd Razali; Pan, Xin Yi; Nordiana, Ahmad Nordin; Anuar, Muhammad; Janifer, Lunyai (AESS Publications., 2023)
The main purpose of this study is to examine the relationship between board diversityand firm value in firms in the manufacturing and non-manufacturing sectors listed onBursa Malaysia. The methodology of this study utilized 200 samples of Malaysian listedcompanies from 2014 to 2016. The board diversity variables in this study were gender,age, educational level, outsider director, and nationality. Diversity data were collectedfrom the annual report, while all financial data, such as firm age, firm value, and firmleverage, were collected from the Eikon database. The findings show that educationallevel has a negative relationship with firm value, while outsider director has a positiverelationship with firm value in the manufacturing sector. In the non-manufacturingsector, gender and nationality have positive relationships with firm value. In conclusion,the manufacturing industry needs outsider directors’ expertise to improve productionoperations. A higher level of education may lead directors to focus on fewer businessaspects rather than the overall business. The non-manufacturing sector requiresknowledge and skills that enhance customer satisfaction and thus increase firm value.The practical implication is that regulators such as Bursa Malaysia can enforceboardroom diversity through rules and regulations, which will affect firm value.